Genealogi dan Strategi Dakwah Kultural NU - Afidatul Asmar (Islamica: Jurnal Studi Keislaman, 2018)
Since Nahdlatul Ulama scholars have been preaching Islamic knowledge using language and the social culture of their audience, the message of preachings (da‘wa) is easily absorbed by the audience. Such Islamic da‘wa is recognised as a cultural Islamic da‘wa, making Islam accommodative to the local culture without reducing any of the values of Islamic principles; and challenging the radical Islamic discourse strongly emerg-ing in post-reformasi Indonesia. This article would revisit the concept of cultural Islamic da‘wa developed by Nahdlatul Ulama scholars, by tracing the strong chains of its genealogies, then exploring the strategies conducted in line with the dream of displaying a “soft” face of Islam in Indonesia. As a result, this article argues that the cultural Islamic da‘wa of Nahdlatul Ulama scholars is inspired by, even adopts to, that of Walisongo in the 15th and 16th centuries Indonesia. Its aim is to make sharī‘ah applicated substantively, other than normatively, by the society, through a strategy of cultural approaches, rather than structural ones.